The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ecoenv.2020.111035
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific air pollutants and meteorological parameters influence COVID-19: A study from mainland China

Abstract: Coronavirus disease 2019 (COVID-19) was first detected in December 2019 in Wuhan, China, with 11,669,259 positive cases and 539,906 deaths globally as of July 8, 2020. The objective of the present study was to determine whether meteorological parameters and air quality affect the transmission of COVID-19, analogous to SARS. We captured data from 29 provinces, including numbers of COVID-19 cases, meteorological parameters, air quality and population flow data, between Jan 21, 2020 and Apr 3, 2020. To evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 41 publications
5
41
0
4
Order By: Relevance
“…While an established correlation between virus transmission and a certain factor is not, in general, a telltale sign of a direct causal relationship between them, in the case of temperature and humidity such connection is firmly indicated also by results of experimental research (Lowen et al, 2007;Casanova et al, 2010;Chan et al, 2011;van Doremalen et al, 2020). Nevertheless, some studies yielded different conclusions, most likely due to the method of calculating R 0 or due to choosing a small/uninformative sample of populations in which the number of infected cases was monitored (Guo et al, 2020;Lin et al, 2020;Yao et al, 2020b). For example, a study focused on the suburbs of New York, Queens, obtained a positive correlation between virus transmission and temperature, which seems unexpected given the prevailing observations of other studies (Adhikari and Yin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While an established correlation between virus transmission and a certain factor is not, in general, a telltale sign of a direct causal relationship between them, in the case of temperature and humidity such connection is firmly indicated also by results of experimental research (Lowen et al, 2007;Casanova et al, 2010;Chan et al, 2011;van Doremalen et al, 2020). Nevertheless, some studies yielded different conclusions, most likely due to the method of calculating R 0 or due to choosing a small/uninformative sample of populations in which the number of infected cases was monitored (Guo et al, 2020;Lin et al, 2020;Yao et al, 2020b). For example, a study focused on the suburbs of New York, Queens, obtained a positive correlation between virus transmission and temperature, which seems unexpected given the prevailing observations of other studies (Adhikari and Yin, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that contaminated air accelerates the transmission of the SARS-CoV-2 to humans other than the transmission from human to human. CO concentration was a risk factor for the increased spreading of SARS-CoV-2, while higher temperature, efficient ventilation and air pressure reduced its transmissibility (26). In another study, after adjusting to temperature and relative humidity, SO 2 , NO 2 , CO, and O 3 , the case fatality rate (CFR) showed a positive association with PM 2.5 and PM 10 in China (27).…”
Section: Coccia (40) Northern Italy Retrospective As Of March 17 To mentioning
confidence: 93%
“…Population flow from Wuhan City may be another potential confounding factor since it may result in disentangled imported or local cases for other Chinese cities. An emerging study found that correlations between gaseous pollutants and R 0 varied in provinces with different population flow (27). However, the effect is likely uniform across cities, and the lockdown of Wuhan mitigated the COVID-19 exportation to other cities effectively.…”
Section: Discussionmentioning
confidence: 99%